PEMBELAJARAN SAINS DI SEKOLAH DASAR BERBASIS KURIKULUM 2013 - Muslimin Ibrahim (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Recently, 2013 curriculum is the best curriculum that have ever had for school in Indonesia. Based on the design, this curriculum comprehend in building human (students) and anticipate for the future. 2013 curriculum is the first curriculum that contain behavior or character explicitly as a competence that must be achieved and organize balancing act between students’ soft skills and hard skill. In addition, Scoring of students’ achievement in learning done comprehensively and continuity use many kinds of strategies that related with competence indicator that will be measured. The success of curriculum in reaching the mission is not only determined by the design, but the important thing is the implementation in the field; realizing the 2013 curriculum in schools. Special for learning science in elementary school must instruct to develop thinking skills and creativity. The teaching learning process focuses on scientific approach and integrated 4 component result study in 2013 curriculum, they are: spiritual attitude, social attitude, creativity, and knowledge. Special for attitude is not only taught verbally, but also by giving good example. Keywords: Science Learning, 2013 Curriculum